2021
DOI: 10.1089/aut.2020.0046
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Parenthood Among Autistic Adults: Implications for Advancing Maternal Health and Parental Well-Being

Abstract: Background: Strikingly little research has considered how autistic adults experience pregnancy and parenthood, two key transition periods in adult development with potentially far-reaching implications for physical and psychosocial health outcomes across the lifespan. This article reviews the research on pregnancy and parenthood among autistic adults, to summarize existing research and identify future directions to advance this critical area of study. Methods: We conducted a systematic review of the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 93 publications
(187 reference statements)
2
7
0
Order By: Relevance
“…49,50 Qualitative studies about autistic parents found that they experienced great joy and intense connections with their children, who were motivators for change and personal growth 21,23,40,51 . In agreement with quantitative studies on this subject 22,33,41,42 , difficulties around communication, judgement and acceptance from professionals were also commonly found.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…49,50 Qualitative studies about autistic parents found that they experienced great joy and intense connections with their children, who were motivators for change and personal growth 21,23,40,51 . In agreement with quantitative studies on this subject 22,33,41,42 , difficulties around communication, judgement and acceptance from professionals were also commonly found.…”
Section: Introductionsupporting
confidence: 83%
“…3,39 Several studies have found that autistic parents experience difficulties regarding effective communication with professionals (while advocating for their children), and in healthcare settings. 22,32,33,[40][41][42] Autistic people are stereotypically believed to lack empathy, mainly due to Theory of Mind research. 43 More recently, researchers have shown that while autistic people may have some difficulty with cognitive empathy or mentalising (understanding someone else's perspective), they have no differences in affective empathy (feelings of love, compassion, concern, and warmth towards others).…”
Section: Introductionmentioning
confidence: 99%
“…Adams and Young, 2021;Raymaker et al, 2017;Maddox et al, 2020;Nicolaidis et al, 2015). It also echoes problems specifically during the perinatal period with attending maternity healthcare highlighted both by McDonnell and DeLucia's (2021) and Grant et al's (2022) reviews. Such barriers to accessing healthcare can lead to adverse outcomes for autistic people (Doherty et al, 2022).…”
Section: Discussionmentioning
confidence: 83%
“…Samuel et al (2022) identified sensory challenges faced by autistic women during pregnancy and birth. McDonnell and DeLucia (2021) examined experiences and outcomes of pregnancy and experiences of parenthood amongst autistic adults, including both mothers and fathers. Grant et al (2022) used qualitative evidence including both peerreviewed primary research and first-hand accounts found in grey literature to explore autistic women's experiences of infant feeding.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Gender diverse autistic people experience higher levels of mental health difficulties compared to both cisgender autistic people 17 and non-autistic gender diverse people, 18 outlining the impacts of being part of multiple marginalized groups on mental health. Autistic women and gender diverse people are also at increased risk of sexual violence 19 and have additional needs related to their health and wellbeing, including sexual and reproductive health, 20 experiences of pregnancy and childbirth, 21 and managing periods and menopause. 22 Despite these additional needs, autistic women and gender diverse people report significantly more barriers to accessing services, 23 including stigma and a lack of knowledge from healthcare providers 24 and are underrepresented in research.…”
Section: Introductionmentioning
confidence: 99%